Improved Productivity of Neutral Lipids in Chlorella sp. A2 by Minimal Nitrogen Supply - Zhu, Junying; Chen, Weixian; Chen, Hui; Zhang, Xin; He, Chenliu; Rong, Junfeng; Wang, Qiang (Frontiers in Microbiology, 2016)
Nitrogen starvation is an efficient environmental pressure for increasing lipid accumulation in microalgae, but it could also significantly lower the biomass productivity, resulting in lower lipid productivity. In this study, green alga Chlorella sp. A2 was cultivated by using a minimal nitrogen supply strategy under both laboratory and outdoor cultivation conditions to evaluate biomass accumulation and lipid production. Results showed that minimal nitrogen supply could promote neutral lipid accumulation of Chlorella sp. A2 without a significant negative effect on cell growth. In laboratory cultivation mode, alga cells cultured with 18 mg L-1 d-1 urea addition could generate 74% and 416% (w/w) more neutral lipid productivity than cells cultured with regular BG11 and nitrogen starvation media, respectively. In outdoor cultivation mode, lipid productivity of cells cultured with 18 mg L-1 d-1 urea addition is approximately 10% and 88% higher than the one with regular BG11 and nitrogen starvation media, respectively. Notably, the results of photosynthetic analysis clarified that minimal nitrogen supply reduced the loss of photosynthetic capacity to keep CO2 fixation during photosynthesis for biomass production. The minimal nitrogen supply strategy for microalgae cultivation could promote neutral lipid accumulation without a significant negative effect on cell growth, resulting in a significant improvement in the lipid productivity.